2012
DOI: 10.2337/db12-0418
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Reversible Mechanisms of Smoking-Induced Insulin Resistance in Humans

Abstract: Smoking is the most common cause of preventable morbidity and mortality in the United States, in part because it is an independent risk factor for the development of insulin resistance and type 2 diabetes. However, mechanisms responsible for smoking-induced insulin resistance are unclear. In this study, we found smokers were less insulin sensitive compared with controls, which increased after either 1 or 2 weeks of smoking cessation. Improvements in insulin sensitivity after smoking cessation occurred with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 52 publications
4
93
0
1
Order By: Relevance
“…Assuming that these associations are causal, the clinical applicability of our study is the identification of modifiable risk factors that can be targeted to improve IS and thereby, potentially attenuate the outcome implications of impaired IS in the CKD population. Supporting this concept, a recent community study showed that chronic cigarette smokers had a lower IS than nonsmokers and that IS improves, although it does not normalize, after 1-2 weeks of smoking cessation (31). Nevertheless, when interpreting these findings, it should be noted that, despite the overall relatively large sample size of the current study, it may not be powered enough to draw firm conclusions in substrata analysis, and additional studies are warranted to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 65%
“…Assuming that these associations are causal, the clinical applicability of our study is the identification of modifiable risk factors that can be targeted to improve IS and thereby, potentially attenuate the outcome implications of impaired IS in the CKD population. Supporting this concept, a recent community study showed that chronic cigarette smokers had a lower IS than nonsmokers and that IS improves, although it does not normalize, after 1-2 weeks of smoking cessation (31). Nevertheless, when interpreting these findings, it should be noted that, despite the overall relatively large sample size of the current study, it may not be powered enough to draw firm conclusions in substrata analysis, and additional studies are warranted to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 65%
“…after 3 months) further deterioration in fasting insulin sensitivity (QUICKI) and fasting hyperinsulinemia, but no change in dynamic insulin sensitivity in the OGTT (OGIS). Two other studies have shown improvements in whole-body insulin sensitivity 1-2 and 8 weeks after stopping smoking respectively (34,35). It is possible that an initial positive effect of smoking cessation on insulin sensitivity (maybe missed in our study on account of the protocol timing) is followed by the deterioration we observed at 3 months -by which time body weight gain was already significant.…”
Section: Insulin Sensitivity and Secretion After Smoking Cessationmentioning
confidence: 56%
“…Insulin sensitivity has been shown to improve with smoking cessation that occurs in conjunction with normalization of phosphorylation of insulin receptor substrate 1 (IRS-1) at Ser636 106 . In cell culture studies, nicotine stimulates the two pathways known to stimulate IRS-1 (Ser636) phosphorylation (p44/42 mitogen-activated protein kinase (MAPK)) and mammalian target of rapamycin (mTOR).…”
Section: Smoking Cessationmentioning
confidence: 99%